Perception of quality nursing care among patient and nurses in a Teaching Hospital - Thulung, B (Journal of Chitwan Medical College, 2017)
This is a descriptive study conducted on patients and nurses in Tribhuvan University Teaching Hospital (TUTH), Kathmandu, Nepal to find out perception of quality nursing care. Structured interview questionnaire for patient and self-administered structure questionnaire for nurses were used to collect data. Main components of quality nursing care included nurses’ visit to the patient, understanding the need of patient, communication of nurses, information during admission procedure, and knowledge and competency of nurses. Highest number (60%) of nurses perceived that they visited patient without calling during their duty hour, but highest number (54%) of patients’ perceived nurses visited them only on request. Ninety six percent of nurses perceived that they communicated with the patient in friendly manner whereas, only 60% patients perceived in the same way. Eighty eight percent of nurses perceived that they provided information about daily routine activities in the hospital whereas; only 62% of patients had the same perception. All nurses perceived that they understood patient’ needs whereas; only 60% patients perceived the same. Similarly 88% nurses perceived that they were knowledgeable and competent, whereas 64% patients perceived nurses were knowledgeable and 72% perceived that nurses were competent.